Contradiction processing in schizophrenia. Issue 6 (2nd November 2018) - Kaliuzhna, Mariia; Langdon, Robyn
ABSTRACT: Introduction: Patients with schizophrenia present clinically with difficulties in manipulating contradictory information in the form of loose associations, surface contradictions and delusional beliefs. It is to date unclear whether patients can detect and process information that contradicts their beliefs and prior knowledge and whether this capacity is related to their symptoms and the nature of contradictory stimuli (e.g., personally significant information, emotional information). Methods: We probed contradiction processing in patients with schizophrenia and healthy controls using sentence verification tasks that involve self-referential judgements (Experiment 1) and general knowledge (Experiment 2), while manipulating the emotional content of the stimuli. Results: We found no differences between patients and controls either on reaction time (Experiment 1 & 2) or accuracy measures (Experiment 1). Conclusions: Our results show no general impairment in contradiction processing in schizophrenia. Rather, failures to detect and correct contradictions in symptoms such as formal though disorder or delusions could arise through a complex interplay between executive dysfunctions, stress and the emotional content of the information.